To lose an empire : British strategy and foreign policy, 1758-90 - Black, Jeremy; Ebook Central (London, England : Zed Books, 2021)
"Bringing strategy, foreign policy, domestic and imperial politics together, this book challenges the conventional understanding as to why the British Empire, at perhaps the height of its power, lost control of its American colonies. Critiquing the traditional emphasis on the value of alliance during the Seven Years' War, and the consequences of British isolation during the War of American Independence, Jeremy Black shows that this rests on a misleading understanding of the relationship between policy and strategy. Encompassing both the Seven Years' War and the American War of Independence and grounded in archival research, this book considers a violent and contentious period which was crucial to the making of modern Britain and its role in the wider world. Offering a reinterpretation of British strategy and foreign policy throughout this time, To Lose an Empire interweaves British domestic policy with diplomatic and colonial developments to show the impact this period and its events had on British strategy and foreign policy for years to come."--
Preface -- Introduction -- 1. The Means of Policy -- 2. The Context of Debate -- 3. To Win America, 1758-604. Winning a Peace, 1761-35. A Post-war Order? 1763-706. Muddling Through? 1771-47. Strategies under Pressure, 1775-88. Strategies Collapse, 1778-829. Picking up the Pieces, 1783-179010. Conclusions -- Bibliography.
Includes bibliographical references (pages 175-177) and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record.
Keywords: Great Britain -- Colonies -- America -- History -- 18th century; Great Britain -- Politics and government -- 1760-1789.; Great Britain -- Foreign relations -- 1760-1789.; History of the Americas,British & Irish history,Military history; Electronic books